Pemberdayaan Masyarakat Penggerak Wisata Berbasis Inovasi BioReefTek dalam Konservasi Terumbu - Yonas Ferdinand Riwu; Junita Cestilia Nenabu; Markus Bunga; Sonnya Marliani (Yumary: Jurnal Pengabdian kepada Masyarakat, 2026)
Purpose: This program aims to enhance the capacity of coastal communities in managing marine ecotourism potential while maintaining the sustainability of coral reef ecosystems. Research Methodology: The implementation methods include socialization, Focus Group Discussions (FGD), technical training, and hands-on practice in the creation and installation of BioReefTek media and spiderwebs as tools for coral growth, involving 48 participants (fishermen and Mitra Analaut) on November 8, 2025. Results: The activities resulted in a significant increase in community knowledge and participation in marine conservation, with a 90% improvement measured through pre-test and post-test evaluations. The FGD produced important recommendations regarding the need for synergy between education, conservation, and nature-based economic development. The active role of the Anana Laut Community was a key element of the program’s success through local innovation and cross-sector collaboration involving the community, academics, government, and private sector. Conclusions: This program demonstrates the effectiveness of a holistic approach in integrating simple technology with local wisdom for the sustainability of coral reef ecosystems. Limitations: The limitation of this community service lies in the use of the BioReefTek method, which requires experimentation with more complex methods for coral ecosystem restoration. Contributions: This program contributes to the preservation of coral reefs, which are better preserved and experiencing improved growth. It also impacts the increased fish catch for fishermen.